Metode Komposting Takakura Untuk Pengolahan Sampah Organik Rumah Tangga Di Cisauk, Tangerang - Renna Eliana; Anastasia Tatik Hartanti; Meda Canti (Universitas Katolik Indonesia Atma Jaya, 2018)
Currently in Cisauk area, there are still a lot of trashes lying on the streets, ditches, rivers, and other public places. The government has encouraged all citizens to sort out garbage and process organic waste into compost. However, not many people comply with this encouragement due to their ignorance or lack of knowledge about practical composting methods. This study aimed to improve social awareness in managing and processing organic domestic waste into compost using Takakura home composting method, which is easy, inexpensive, and odorless. Moreover, different home-made compost starters with different mixed microbial inoculants were compared. The study included microbial inoculant preparation, home-made compost starter production from rice husk and rice bran, and compost production in Takakura basket. The methods were taught through a series of workshop in Bermis Serpong Asri Residence, Cisauk, Tangerang. Through this effort, the problem of domestic organic waste was expected to be overcome. Moreover, the product of Takakura home composting can be used as plant and soil fertilizer, or even sold to increase family income.